Risk Assessment on Loading and Unloading Heavy Material in Non-Destructive Testing Industry - ATIKA RAMADHANI BINTI SURYADI; AMIR HAZIQ BIN ABDUL RAZAK; MUHAMMAD SYAKIR YATIMY BIN MOHD ZOLKAFLY (Progress in Engineering Application and Technology, 2025)
Heavy material loading and unloading are critical activities in many industries, often associated with significant safety risks. Proper hazard identification, risk assessment, and risk control (HIRARC) are essential to minimize these risks and ensure a safe working environment. This study aimed to identify potential hazards associated with the loading and unloading of heavy materials activity, to assess risk assessment that related with loading and unloading heavy material activity using the HIRARC assessment form and to propose effective risk control measures of loading and unloading heavy material activity and improve workplace safety. The research integrated qualitative and quantitative methods such as field observation and semi-structured interviews. The HIRARC methodology is applied systematically to evaluate risks and recommend controls. The study identifies improper technique of lifting, exposed to sharp edges, improper design of trolley and exposed to dust as the primary risks during loading and unloading operations. Risk assessments reveal to medium. Mitigation strategies such as use rust-resistant material for block, provide a clear SOP and use a cut-resistant glove and safety shoes are proposed to address these challenges. By implementing the HIRARC framework, workplaces can effectively manage and mitigate hazards, reducing the likelihood of incidents and fostering a safer working environment. This research contributes to improving safety practices in industries reliant on heavy material handling operations.